2019
DOI: 10.1002/bies.201900008
|View full text |Cite
|
Sign up to set email alerts
|

Lactate: A Novel Signaling Molecule in Synaptic Plasticity and Drug Addiction

Abstract: l‐Lactate is emerging as a crucial regulatory nexus for energy metabolism in the brain and signaling transduction in synaptic plasticity, memory processes, and drug addiction instead of being merely a waste by‐product of anaerobic glycolysis. In this review, the role of lactate in various memory processes, synapse plasticity and drug addiction on the basis of recent studies is summarized and discussed. To this end, three main parts are presented: first, lactate as an energy substrate in energy metabolism of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 125 publications
(215 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, lactate and phosphocholine remained elevated 48 h after dosing. The involvement of lactate in synaptic plasticity hints at a direct role in consolidating drug‐related memories (Hillard, 2005; Wang et al, 2019). Astrocyte‐neuron lactate transport in the basolateral amygdala is critical for the reconsolidation of cocaine memory, and strategies reducing lactate concentrations (by blocking glycogenolysis in astrocytes) in the basolateral amygdala of mice undergoing a conditioned‐place preference paradigm have been shown to prevent the establishment of cocaine‐induced conditioned‐place preference and to decrease cocaine self‐administration (Zhang, Xue, et al, 2016).…”
Section: Metabolic Phenotyping Of Psychostimulant Addictionmentioning
confidence: 99%
“…Interestingly, lactate and phosphocholine remained elevated 48 h after dosing. The involvement of lactate in synaptic plasticity hints at a direct role in consolidating drug‐related memories (Hillard, 2005; Wang et al, 2019). Astrocyte‐neuron lactate transport in the basolateral amygdala is critical for the reconsolidation of cocaine memory, and strategies reducing lactate concentrations (by blocking glycogenolysis in astrocytes) in the basolateral amygdala of mice undergoing a conditioned‐place preference paradigm have been shown to prevent the establishment of cocaine‐induced conditioned‐place preference and to decrease cocaine self‐administration (Zhang, Xue, et al, 2016).…”
Section: Metabolic Phenotyping Of Psychostimulant Addictionmentioning
confidence: 99%
“…Elevated brain lactate and glutamate levels are associated with wakefulness and memory formation, which naturally require the processing of incoming sensory stimuli, like the control exerted by the central visual pathways for either gating or filtering out behaviorally relevant or irrelevant visual information. As such, the metabolic responses to perceived, but not unperceived, sensory stimulation could be enabling factors for learning and memory, as indicated by the relevance of aerobic glycolysis and lactate in synaptic plasticity mechanisms ( Bueschke et al, 2021 ; Descalzi et al, 2019 ; DiNuzzo, 2016 ; Harris et al, 2019 ; Herrera-López et al, 2020 ; Jourdain et al, 2018 ; Kobayashi et al, 2019 ; Lundquist et al, 2021 ; Margineanu et al, 2018 ; Scavuzzo et al, 2020 ; Wang et al, 2019 ; Yang et al, 2014 ). In particular, aerobic glycolysis and lactate might reflect cortical information processing and, in turn, intracortical communication, in agreement with the relation between regional metabolic rates of glucose utilization and resting-state network dynamics in the cerebral cortex ( Jamadar et al, 2020 ; Noack et al, 2017 ; Spetsieris et al, 2015 ; Su et al, 2018 ; Thompson, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the decrease of pyruvate in PABS did not prevent its upregulation in TCA cycle, and the lactic acid level in ABS was also significantly lower than it was in HCs and PABS. Recently, lactic acid has been considered a new type of signaling molecule involved in many key reactions, and it plays an indispensable role in learning and memory, which may be related to drug addiction [ 56 , 57 ]. Lactate at physiological concentrations functions as a signaling molecule instead of an energy substrate [ 57 ], and studies have shown that peripheral administration of lactic acid produces antidepressant-like effects in different animal models of depression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lactic acid has been considered a new type of signaling molecule involved in many key reactions, and it plays an indispensable role in learning and memory, which may be related to drug addiction [ 56 , 57 ]. Lactate at physiological concentrations functions as a signaling molecule instead of an energy substrate [ 57 ], and studies have shown that peripheral administration of lactic acid produces antidepressant-like effects in different animal models of depression [ 58 ]. This finding suggests that the low lactate level may be closely related to acute withdrawal.…”
Section: Discussionmentioning
confidence: 99%